Exploring Determinants Contributing to Disputes in the Closing of Final Accounts in the Construction Industry - Othman, Mohd Khairul Fitri; Judi, Siti Suhana; Ismail, Zulhabri; Sui Pheng, Low (International Journal of Sustainable Construction Engineering and Technology, 2023)
The closing of final accounts without any disputes that satisfy all stakeholders is an important factor in measuring the success of a construction project, as it ensures that all financial matters are settled in a fair and transparent manner. It also provides an opportunity for the contracting parties (contractor and client) to reconcile their records and resolve any differences to ensure that the project is completed within budget. However, the closing of final accounts in the Malaysian construction industry has long been a problematic issue where settlements often take much longer than stipulated in the contract due to disputes and a lack of attention to settling the final accounts in a timely manner. This study aims to identify the determinants that constrain prompt settlement and contribute to disputes in the closing of final accounts as part of a broader research project. An extensive literature review was conducted to obtain relevant information relating to final accounts in the construction industry and the major determinants contributing to disputes in the closing of final accounts. The results suggest that the major determinants contributing to disputes in the closing process of final accounts can be categorised into seven aspects, namely: client, contractor, contractual, management, variation, human behaviour, and environmental/external. Through this research, a conceptual framework is proposed to serve as a reference for stakeholders to reduce disputes in the closing of final accounts. The findings of this research contribute to existing knowledge relating to issues in final accounts and enhance the understanding and awareness of contracting parties on the determinants that lead to disputes, thereby enabling them to prevent such conflicts at an early stage in construction projects. This ultimately serves to improve the closing process of final accounts in the Malaysian construction industry.